Estimating the PDMS-coated, SPME-fibre/water- and fibre/gas-partition coefficients of chlorinated ethenes by headspace-SPME - Salaices Avila, Manuel Alejandro; Breiter, Roman (Chromatographia, 2007)
In this work, a simple, fast and reproducible method is presented for the determination of fibre/liquid-phase and fibre/gas-phase partition coefficients of five chlorinated ethenes on a poly-(dimethylsiloxone), PDMS-coated, solid-phase microextraction fibre, by employing a headspace HS-SPME coupled with gas chromatography. The partition coefficients were estimated by a numerical method using a Level-I fugacity method coupled with parameter-estimation software. Dimensionless partition coefficients between SPME fibre and liquid as well as gas phases were obtained at temperatures of 10 degrees C, 25 degrees C and 30 degrees C. The partition coefficients of the fibre and the gas phase, K-fg, increase with decreasing temperature by a factor of approximate to 2 to 6, and they are directly proportional to the linear slope of the regression line. The same tendency is observed for the partition coefficient of the fibre and liquid phase, K-fw, in a factor approximate to 1.2 to 2.0. The sorption enthalpy is higher in the gas phase; therefore, the sorption onto the fibre is favoured at lower temperatures. The correlation of the log K-ow versus log K-fw and log K., versus log K-fg shows a linear relationship with the number of chlorine atoms in the C = C molecule. Long-term experiments resulted in sorption to Teflon surfaces and possible losses in 43 mL vials, not observed in 250 mL Boston bottles.
Keywords: gas chromatography; solid-phase microextraction; headspace chromatography; partition coefficient; chlorinated ethenes; fugacity